2023
DOI: 10.1148/radiol.222730
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vaccination and the Omicron Variant on COVID-19–related Chest CT Findings: A Multicenter Study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) omicron variant has a higher infection rate than previous variants but results in less severe disease. However, the impacts of omicron and vaccination on chest CT findings are difficult to evaluate. Purpose To investigate the impact of vaccination status and predominant variant on chest CT findings, diagnostic and severity scores in multicenter sample of consecutive patients referred to emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…The study provided more robust evidence on the independent associations of vaccination and Omicron with the CT manifestations of COVID-19 ( 8 ). Omicron has been found to replicate more efficiently in the bronchi than in the lung parenchyma compared with other variants ( 6 ), and vaccination enhances immunity, inhibiting viral replication.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…The study provided more robust evidence on the independent associations of vaccination and Omicron with the CT manifestations of COVID-19 ( 8 ). Omicron has been found to replicate more efficiently in the bronchi than in the lung parenchyma compared with other variants ( 6 ), and vaccination enhances immunity, inhibiting viral replication.…”
mentioning
confidence: 85%
“…While vaccine effectiveness against SARS-CoV-2 infection decreases over time (from 83% in the first month to 22% at 5 months or longer for all infections; from 94% to 64% for symptomatic infections), vaccine effectiveness against severe infection remains well-maintained, at around 90%, at 5 months or longer ( 9 ). In line with the prolonged effectiveness against severe infections, Crombé et al found that the proportions of patients with no pneumonia, typical CT findings, and severe pneumonia involving at least 25% of the lung parenchyma remained stable regardless of the interval between vaccination and infection (up to 6 months or longer) ( 8 ). This may imply that vaccine effectiveness against pneumonia resembles the protection from severe infections, rather than the protection from all infections, and may wane to a lesser extent than against SARS-CoV-2 infection itself.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Coronavirus disease 2019 (COVID-19) has become endemic worldwide. Latest radiological researches on COVID-19 have shown that the omicron strain and especially the newer omicron variant (BA.5) of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to higher rates of transmission and decreased severity of infection, subsequently acting as an endemic viral infection [ 1 3 ]. To better anticipate the next pandemic, health agencies investigated the first weeks of the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%